STRATEGI PENGEMBANGAN EKOWISATA BERKELANJUTAN DI KALIMANTAN TENGAH: TINJAUAN KONSEPTUAL DAN EMPIRIS - Saputra, Putu Wisnu (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2025)
Ecotourism is a form of sustainable tourism that emphasizes environmental conservation and the enhancement of local community welfare. This article explores the development of ecotourism in Central Kalimantan using a literature review approach to examine its potential, challenges, and strategies through collaborative and digital-based models. Central Kalimantan possesses rich biodiversity, distinctive local culture, and conservation areas such as Tanjung Puting and Sebangau National Parks, making it a promising region for ecotourism development. The study reveals existing gaps between policy, implementation, and community participation. Therefore, a shift is needed from a top-down to an integrative approach involving government, local communities, private sector, academia, and digital technology utilization. This model is believed to enhance the ecological, social, and economic resilience of local communities. The article contributes theoretically to the discourse of ecotourism management and provides practical policy implications to support the development of locally-based, adaptive, and sustainable tourism destinations. The findings highlight that the success of ecotourism strongly relies on multi-stakeholder synergy and strategically integrated digital adoption. Keywords : Development, Ecotourism, Sustainable.